2019
DOI: 10.1186/s13256-019-2257-7
|View full text |Cite
|
Sign up to set email alerts
|

Giant parathyroid adenoma: a case report and review of the literature

Abstract: BackgroundGiant parathyroid adenoma is a rare type of parathyroid adenoma defined as weighing > 3.5 g. They present as primary hyperparathyroidism but with more elevated laboratory findings and more severe clinical presentations due to the larger tissue mass. This is the first reported case of giant parathyroid adenoma from the Middle East.Case presentationA 52-year-old Indian woman presented with a palpable right-sided neck mass and generalized fatigue. Investigations revealed hypercalcemia with elevated para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
0
36
0
4
Order By: Relevance
“…3 Although the average size of a giant parathyroid adenoma is 5.65 grams, they rarely exceed 30 grams in weight with very few reports describing weights up to 110 grams. 3,4 Thus, our 37-gram adenoma is likely >99th percentile in size and weight. More interestingly, our giant adenoma was associated with a right ASA and NRLN and one of the presenting symptoms was severe headaches.…”
Section: Discussionmentioning
confidence: 91%
“…3 Although the average size of a giant parathyroid adenoma is 5.65 grams, they rarely exceed 30 grams in weight with very few reports describing weights up to 110 grams. 3,4 Thus, our 37-gram adenoma is likely >99th percentile in size and weight. More interestingly, our giant adenoma was associated with a right ASA and NRLN and one of the presenting symptoms was severe headaches.…”
Section: Discussionmentioning
confidence: 91%
“…TE et al reported in his prospective database study a percentage of 10.7% from 519 patients for giant adenomas over eleven years despite using 3 g as their cutoff point for giant adenomas compared to our 3.5 g [ 13 ]. Also, five patients in our cohort presented with giant adenomas weighing over 10 g, the maximum was 32 g. These giant adenomas are unusual and were presented only as case reports in the literature [ 23 , 24 ]. These elevated numbers are more likely to be inflated as a result of the lack of routine calcium screening rather than PTAs displaying unique hyperproliferative patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical presentation of giant parathyroid adenoma is mostly similar to parathyroid adenoma. However, while parathyroid adenomas (PAs) is usually asymptomatic, GPA is mostly symptomatic (4,5). The classic constellation of symptoms is rarely seen these days due to frequent routine chemical assessment and timely intervention.…”
Section: Discussionmentioning
confidence: 99%